An efficient and reliable method for measuring cerebral lateralization during speech with functional transcranial Doppler ultrasound - Bishop, D; Watt, H; Papadatou-Pastou, M (Elsevier, 2009)
The gold standard method for measuring cerebral lateralization, the Wada technique, is too invasive for routine research use. Functional magnetic resonance imaging is a viable alternative but it is costly and affected by muscle artefact when activation tasks involve speech. Functional transcranial Doppler ultrasonography (fTCD) can be used to assess cerebral lateralization by comparing blood flow in the middle cerebral arteries. We used fTCD to compare indices of language lateralization in 33 adults in three different paradigms: Word Generation, Picture Description and a shorter Animation Description task. Animation Description gave valid results, and we subsequently demonstrated its reliability in a group of 21 4-year-old children. Cerebral lateralization during spoken language generation can be assessed reliably and cheaply using fTCD with a paradigm that is less taxing than the traditional word generation paradigm, does not require literacy skills and can be completed in 15 min or less.